Navigating turbulence, sustaining growth - World Bank (Springer, 2015)
The World Bank East Asia and Pacific Economic Update is a comprehensive, twice-yearly review of the region's economies prepared by the East Asia and Pacific region of the World Bank. In 2011, an estimated 38 million people will move out of poverty, and the proportion of people living on less than US $2 a day expected to decrease to about 24 percent, down two percentage points from 2010. Growth in developing East Asia in the first half of 2011 continued to moderate, mainly due to weakening external demand.